2021
DOI: 10.21037/apm-20-2481
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study to predict distant metastasis in patients with renal cell carcinoma

Abstract: Background: Nomogram is potentially applied for quantitatively evaluating the probability of distant metastasis. The objective of our research was to establish a nomogram to predict distant metastasis in renal cell carcinoma (RCC) patients. Methods: We conducted a retrospective analysis on 37,190 RCC cases diagnosed between 2010 and 2015 in the Surveillance Epidemiology and End Results (SEER) database. A multivariate logistic regression model-based nomogram was applied for predicting the risk factors concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Several clinicopathological parameters have been identified to establish the nomogram for predicting SDM of ccRCC patients ( 7 , 8 ): T stage, pathological differentiation grade, lymph node status, tumor size, and the invasion beyond the capsule. One of the most meaningful risk factors is the tumor size of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinicopathological parameters have been identified to establish the nomogram for predicting SDM of ccRCC patients ( 7 , 8 ): T stage, pathological differentiation grade, lymph node status, tumor size, and the invasion beyond the capsule. One of the most meaningful risk factors is the tumor size of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to accurately predict the risk of metastasis in patients, strengthening doctors' active monitoring of patients and preventing distant metastasis early. (32) used patients in the SEER database to predict distant metastasis in RCC patients, but the C index was only 0.863. As far as we know, the current prediction model for distant metastases in RCC patients using nomograms has defects of a small number of patients and low prediction accuracy (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of distant metastasis was significantly increased when tumor size was more significant than 3 cm. Li et al constructed a nomogram to predict distant metastasis of RCC and found that tumors larger than 3 cm would increase the risk of metastasis (32).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, clear cell RCC accounted for 82% of all RCC metastases, which is in keeping with the overall frequency of clear cell RCC [ Figure 5a ]. [ 58 ] Ancillary immunohistochemical studies are frequently performed to support the morphologic diagnosis. Clear cell RCC expresses PAX8, CD10, CAIX, RCC, epithelial markers (cytokeratins AE1/AE3 and CAM5.2 and EMA), and vimentin [Figure 5b - d ].…”
Section: Discussionmentioning
confidence: 99%